The Hidden Fields in Material that used for Building (Journal of Engineering, 2024)
n the Last Recent Years, the Conservation of Natural Environment Resources be a Problem that to and fro to get a line between two elements, First of one is the Natural Environment Resources Balance, and the other is the Reduction of its Consumption and Limitation of Negative Results upon this Environment, Last Years seeks to but Modern Architecture Concept to Conservator Energy Resources and Natural Sources To Reach that Known Sustainable Buildings Which have the Lessees Effect on the Natural Environment and its Environmental Properties.On the Concern that Materials is the Main Component of Architectural Configuration and appearance that Architect use it in Sustainable Construction to redecate the Environmental effect and to establish a complete constructing experience in Architectural Field in the same Time it been the Basic stone effected the nature by reducting its recourses continually, and thrown Tons of Wastes in Trash areas on the Roods Edges, Resulted the abuse of Hectares of Agricultural lands. this Dangerous Trashes accumulated without any treatment in most of Countries, that Generate Negative reaction Power upon this Environment because of Chemical Interactions of This materials (Trashes) between each and other.Therefore. The study directed in its Problem to Illustrate the Identity and Nature of Projected Power that Causes the accumulation Tons of Materials and Resulting the action of Change in Material and the Natural of Reaction Generated from Material that Causes Pollution Research aims to put Sustainable Building (in the point of view of Material that constructs it) in front of nature of Forces that causes Material Change and Changes Through the Running Time of Building age and so.....to Have a Wide Lines on Effected Forces of the same Materials that used in Buildings and causes Environmental Pollution , Today used in the Sustainable Buildings but in the Form that Reeducate the Environmental Pollution of it.The Research based on the study of Power's Nature That effected materials and influenced by , and its effects on the Environment system, to be the case study of this study.